Potassium silicate as an inducer of abiotic stress resistance in grain sorghum seeds - Rayane Pinheiro, Paloma (Revista Ciência Agronômica, 2021)
Sorghum is an important crop that can absorb and accumulate abundant Si ranging, improving tissue tolerance to the water and salt stress and reducing sodium absorption. T hus, the objective was to verify the induction of resistance in germination and seedling growth of sorghum seeds to salt and water stress during germination due to treatment with silicon. Two experiments were carried out with seeds of two sorghum cultivars (EA03 and EA955) were solution of potassium silicate solutions at concentrations of 0, 0.3, 0.6, 0.9 and 1.2 g L-1, in the first experiment and seeds were submitted to water stress using PEG 6000 (0, -0.2, -0.4, -0.6 and -0.8 MPa) in the second experiment were submitted to salt stress using NaCl (0, 75, 150 and 225 mM). Were analysed, germination, first germination count, shoot and root length, shoot to root ratio and seedling dry weight. The studied genotypes showed similar behavior when treated with potassium silicate. The presence of silicon in the treatment of seeds when exposed to salt stress has no effect on germination, but attenuates salinity damage related to seedling growth. Silicon attenuates the effects of water stress on sorghum seeds, by maintaining germination up to the potential of -0.6 Mpa, and providing better root development. However, the treatment with potassium silicate does not prevent the damage caused by high levels of water and salt stress, only attenuating its effects, thus, more studies are needed to better clarify the effects of Si on seeds.